Profiling of WDR36 Missense Variants in German Patients with Glaucoma - Passuto, Francesca (2008)
PURPOSE. Mutations in WDR36 were recently reported in patients with adult-onset primary open-angle glaucoma (POAG). In this study, the prevalence of WDR36 variants was investigated in patients with glaucoma who were of German descent with diverse age of onset and intraocular pressure levels. METHODS. Recruited were 399 unrelated patients with glaucoma and 376 healthy subjects of comparable age and origin, who had had repeated normal findings in ophthalmic examinations. The frequency of observed variants was obtained by direct sequencing of the entire WDR36 coding region. RESULTS. A total of 44 WDR36 allelic variants were detected, including 14 nonsynonymous amino acid alterations, of which 7 are novel (P31T, Y97C, D126N, T403A, H411Y, H411L, and P487R) and 7 have been reported (L25P, D33E, A163V, H212P, A449T, D658G and I264V). Of these 14 variants, 6 were classified as polymorphisms as they were detected in patients and control individuals at similar frequencies. Eight variants present in 15 patients (3.7%) but only 1 control individual (0.2%) were defined as putative disease-causing variants (P 0.0005). Within this patient group, 12 (80%) presented with high and 3 (20%) with low intraocular pressure. Disease severity and age of onset showed a broad range. CONCLUSIONS. The occurrence of several rare putative diseasecausing variants in patients with glaucoma suggests that WDR36 may be a minor disease-causing gene in glaucoma, at least in the German population. The large variability in WDR36, though, requires functional validation of these variants, once its function is characterized.